Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. (Policy Papers; Policy Paper ;, 2005)
This report provides an update on the work and direction of the Fund since the 2005 Spring Meetings. Since that time, the global economy has enjoyed strong growth--albeit with significant regional differences--and an absence of major financial crises, even though growing imbalances and rising oil prices have clouded the outlook. Although some steps the Fund has been advocating for some time have been taken--for example, increased flexibility in exchange rate regimes in Asia-decisive action to reduce global imbalances has remained elusive. At the same time, progress toward the Millennium Development Goals MDGs) remains slow and uneven,1 highlighting the need for concerted action by all countries. Further impetus is also urgently needed to move the Doha Round of trade negotiations toward an ambitious conclusion.